Retorika Gaya Motivator dalam Pemberian Motivasi - Desember, Sella; Sari, Wulan Purnama (Koneksi, 2022)
Rhetoric in communication is very necessary, because rhetoric is the basis for us to train our way of speaking to a wide audience. Rhetoric is also needed in the social, political, economic and educational fields. Rhetoric is very important for the motivator in conveying his motivational message. Apart from speaking the words motivator also requires oculesic and kinesic in the delivery. Motivators and characters are usually given great attention when it comes to conveying messages or words. The I'M POSSIBLE program on MetroTV, hosted by Merry Riana as a host as well as a motivator, is an inspiring, educational and motivating program. At the I'M POSSIBLE event, the writer saw that in giving motivation from Merry Riana there were aspects of rhetoric in it, because the delivery was not heavy and the topics presented were very relevant to all people then the colorful way of delivery made this program not boring. Therefore, the writer examines the rhetoric of motivator style in giving motivation (analysis on Merry Riana in the event I'M POSSIBLE on MetroTV). Based on a discussion that includes rhetoric on motivators, this study uses qualitative case study methods and semiotics to analyze every word and motion given by Merry Riana. Retorika dalam komunikasi sangat diperlukan, karena retorika merupakan dasar untuk individu melatih cara bicara di depan khalayak. Retorika juga diperlukan pada bidang sosial, politik, ekonomi dan pendidikan. Retorika sangat penting bagi motivator dalam menyampaikan pesan motivasinya. Selain bertutur kata motivator juga memerlukan okulesik dan kinesik dalam penyampaianya. Motivator dan para tokoh biasanya sangat diperhatikan dalam hal dia menyampaikan pesan atau kata-kata. Program acara I’m Possible di MetroTV yang dibawakan oleh Merry Riana sebagai pemandu acara sekaligus motivator merupakan sebuah program acara yang inspiratif, edukatif, dan memotivasi. Pada acara I’m Possible ini penulis melihat dalam pemberian motivasi dari Merry Riana terdapat aspek-aspek retorika didalamnya, karena penyampaiannya yang tidak berat dan topik yang dibawakan sangat relevan untuk semua masyarakat kemudian cara penyampaiannya yang penuh warna membuat program acara ini tidak membosankan. Maka dari itu, penulis meneliti retorika gaya motivator dalam pemberian motivasi pada Merry Riana dalam acara I’m Possible di MetroTV. Berdasarkan pembahasan yang meliputi retorika pada motivator, penelitian ini menggunakan metode studi kasus kualitatif dan semiotika untuk menganalisa setiap kata-kata dan gerak yang diberikan oleh Merry Riana.